Positive electrode sheet, secondary battery, battery module, battery pack and power-consuming device
Patent Information
- Application Number
- CN202111125842.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-23
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-09-23
AI Technical Summary
The existing lithium-ion secondary batteries have a slow removal rate during drying, resulting in high water content of the battery, affecting circulation and safety performance.
Ionic and nonionic surfactants are added as water removal agents to the coating of the positive electrode sheet to increase the vapor pressure of the moisture stored between the particles, thereby accelerating the volatility of the moisture.
通过提高除水速率,降低了二次电池的含水量,改善了循环性能和安全性能,同时减少了生产能耗。
Smart Images

Figure CN115832218B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a positive electrode sheet, a secondary battery, a battery module, a battery pack and an electrical device. Background Art
[0002] In recent years, as the application scope of lithium-ion secondary batteries becomes wider and wider, lithium-ion secondary batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As lithium-ion secondary batteries have made great progress, higher requirements have been put forward for their energy density, cycle performance and safety performance. The industry stabilizes the structure of the material itself and reduces the amount of residual lithium on the surface of the material by modifying the cathode material by bulk doping and surface coating, or adds film-forming agents to the electrolyte to reduce the side reactions on the surface of the material, thereby inhibiting the gas production inside the lithium-ion secondary battery and improving the cycle performance and safety performance of the lithium-ion secondary battery. Summary of the invention
[0003] Technical problem to be solved by the invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a positive electrode plate, which has a faster water removal rate during the drying process, thereby being able to reduce the water content of the secondary battery containing the positive electrode plate, so that the secondary battery has better cycle performance and safety performance.
[0005] Technical solutions to solve problems
[0006] In order to achieve the above-mentioned objectives, the present application provides a positive electrode plate, a secondary battery, a battery module, a battery pack and an electrical device.
[0007] The first aspect of the present application provides a positive electrode plate, which includes: a current collector and a coating coated on at least one surface of the current collector, the coating including a positive electrode active material and a dehydrating agent, the positive electrode active material is lithium iron phosphate, and the weight proportion of the dehydrating agent relative to the total solid content of the coating is 0.02 to 2.0%, optionally, 0.09 to 0.3%.
[0008] Therefore, the inventors of the present application discovered through a large number of experiments that by adding a desiccant to the coating of the positive electrode plate, the desiccant can increase the saturated vapor pressure of water accumulated between the particles in the positive electrode plate, thereby accelerating the evaporation of water in the positive electrode plate, further increasing the desiccant rate of the positive electrode plate, and improving the cycle performance and safety performance of the secondary battery containing the positive electrode plate.
[0009] In any embodiment, the dehydrating agent may be at least one of a nonionic surfactant and / or an ionic surfactant.
[0010] In any embodiment, the ionic surfactant may be at least one of sulfate and / or alkylphenyl sulfonate. Optionally, the sulfate may be at least one of sodium sulfate and potassium sulfate, and the alkylphenyl sulfonate may be at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and potassium perfluorooctane sulfonate.
[0011] And / or, the nonionic surfactant may be octylphenol polyoxyethylene ether or polyvinyl pyrrolidone.
[0012] It should be noted that there are ionic and non-ionic surfactants according to the hydrophilic group. Specifically, non-ionic surfactants refer to surfactants whose molecules contain ether groups that do not dissociate in aqueous solution as the main hydrophilic group, and their surface activity is reflected by neutral molecules; ionic surfactants refer to surfactants whose hydrophilic groups are ionic groups. When ionic surfactants are dissolved in water, they can ionize to generate anions and cations.
[0013] Therefore, the present application increases the vapor pressure of water stored between particles in the positive electrode plate by selecting the above-mentioned specific non-ionic surfactants and ionic surfactants, and can also reduce the water content of the secondary battery, thereby improving the cycle performance and safety performance of the secondary battery.
[0014] In any embodiment, the total weight ratio of the lithium iron phosphate and the dehydrating agent is 95-98% relative to the total weight of the coating. Thus, when the total weight of the lithium iron phosphate and the dehydrating agent is within the above range, the dehydrating agent can exert a good dehydration effect, accelerate the volatilization of water in the positive electrode plate, improve the cycle performance and safety performance of the secondary battery, and do not affect the energy density of the secondary battery using the positive electrode plate.
[0015] In any embodiment, the compaction density of the positive electrode sheet is 2.35 to 2.6 g / cm 3 Therefore, when the compaction density of the positive electrode sheet is within the above range, the pores of the positive electrode sheet are moderate, which accelerates the volatilization of water during the baking process.
[0016] In addition, the water content of the positive electrode plate can be measured according to the Karl Fischer coulometric method of GB / T11133-2015.
[0017] The compaction density test method of the positive electrode is:
[0018] Cut the positive electrode into a size of 1540.25mm 2 Use a small disc to weigh and measure the thickness of the positive electrode.
[0019] Compacted density = total coating weight CW / (positive electrode sheet thickness - current collector thickness)
[0020] A second aspect of the present application provides a secondary battery, comprising the positive electrode sheet of the first aspect of the present application.
[0021] A third aspect of the present application provides a battery module, comprising the secondary battery of the second aspect of the present application.
[0022] A fourth aspect of the present application provides a battery pack comprising the battery module of the third aspect of the present application.
[0023] The fifth aspect of the present application provides an electrical device comprising at least one selected from the secondary battery of the second aspect of the present application, the battery module of the third aspect of the present application, or the battery pack of the fourth aspect of the present application.
[0024] Effects of the Invention
[0025] The present application provides a positive electrode sheet, a secondary battery, a battery module, a battery pack and an electric device. An ionic surfactant and / or a nonionic surfactant is added to the coating of the positive electrode sheet as a dehumidifier; the dehumidifier can increase the vapor pressure of the water stored between the particles in the positive electrode sheet, accelerate the drying rate of the positive electrode sheet, thereby reducing the water content of the secondary battery using the positive electrode sheet, thereby improving the cycle performance and safety performance of the secondary battery. At the same time, the production energy consumption of the secondary battery is reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the cycle exchange performance diagram of Example 1 and Comparative Example 3 of the present application.
[0027] Figure 2 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0028] Figure 3 yes Figure 2 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0029] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application.
[0030] Figure 5 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0031] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0032] Figure 7 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0033] Description of reference numerals:
[0034] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION
[0035] Below, the embodiments of the positive electrode plate, secondary battery, battery module, battery pack and electrical device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0036] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3,4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0037] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0038] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0039] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0040] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0041] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0042] In one embodiment of the present application, the present application proposes a positive electrode plate, which includes: a current collector and a coating coated on at least one surface of the current collector, the coating includes a positive electrode active material and a dehydrating agent, the positive electrode active material is lithium iron phosphate, and the weight proportion of the dehydrating agent relative to the total solid content of the coating is 0.02 to 2.0%, optionally, 0.09 to 0.3%.
[0043] The saturated vapor pressure of water satisfies the following formula:
[0044]
[0045] In the formula, P0: saturated vapor pressure on the plane; P: saturated vapor pressure of droplets or small bubbles (when the liquid is a concave liquid surface, r<0); ρ: liquid density; M: molar mass γ: surface tension; R: gas constant; T: thermodynamic temperature.
[0046] The surface tension in a capillary tube has the following relationship:
[0047]
[0048] In formula (2), r' is the capillary radius; h is the capillary liquid level; cosθ is the contact angle.
[0049] Combining equation (1) and equation (2) yields the following result:
[0050]
[0051] It can be seen from formula (3) that the saturated vapor pressure of the liquid in the pore structure is related to the liquid level in the capillary; the lower h is, the larger P is; and the liquid level is directly related to the surface tension, contact angle and capillary radius. Therefore, the evaporation speed of water is positively correlated with its saturated vapor pressure. From the perspective of the positive electrode, there are a large number of pore structures between the main material powders in the coating, which will lead to the existence of capillary action, and the water in the pore structure is difficult to evaporate. Therefore, the present application attempts to accelerate the evaporation of water by introducing additives in order to improve the capillary action of water in the pores of the electrode.
[0052] The inventors of the present application have found that the water content of the positive electrode plate of a lithium-ion secondary battery has a great influence on its cycle performance and safety performance. The electrolyte usually uses lithium hexafluorophosphate as the electrolyte, but lithium hexafluorophosphate is very sensitive to moisture and easily decomposes when exposed to water. It not only consumes active lithium ions and affects the cycle performance of the lithium-ion secondary battery, but also decomposes to produce corrosive gases such as hydrofluoric acid, which corrode the outer shell of the lithium-ion secondary battery. Therefore, it is very important to reduce the water content in the positive electrode plate.
[0053] Although the mechanism is not clear, the applicant unexpectedly found that: the present application adds an ionic surfactant and / or a non-ionic surfactant to the coating of the positive electrode plate as a dehydrating agent; the dehydrating agent can increase the vapor pressure of the water stored between the particles in the positive electrode plate, accelerate the dehydration rate of the positive electrode plate, thereby reducing the water content of the battery cell using the positive electrode plate, thereby improving the cycle performance and safety performance of the secondary battery. At the same time, the production energy consumption of the secondary battery is reduced.
[0054] In some embodiments, from the perspective of increasing the saturated vapor pressure of water stored between particles in the positive electrode sheet, the dehydrating agent may be a non-ionic surfactant and / or an ionic surfactant.
[0055] In some embodiments, the ionic surfactant is at least one of sulfate and alkylphenyl sulfonate, and optionally, the sulfate is at least one of sodium sulfate and potassium sulfate, the alkylphenyl sulfonate is at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and potassium perfluorooctane sulfonate, and / or the non-ionic surfactant is at least one of octylphenol polyoxyethylene ether and polyvinyl pyrrolidone.
[0056] The dehydrating agent has stable chemical properties, is soluble in water and does not react with other components in the positive electrode plate, and has a melting point, boiling point and decomposition temperature greater than 200° C. Therefore, the present application increases the vapor pressure of water stored between particles in the positive electrode plate by selecting the above-mentioned specific non-ionic surfactant and ionic surfactant, and can also reduce the water content of the secondary battery, thereby improving the cycle performance and safety performance of the secondary battery.
[0057] In some embodiments, the total weight ratio of the lithium iron phosphate and the dehydrating agent is 95-98% relative to the total weight of the coating. Figure 1 When the total weight ratio of the dehydrating agent to the lithium iron phosphate is within the above range, the dehydrating agent has a good dehydrating effect, accelerating the volatilization of moisture in the positive electrode sheet, and the battery cell formed by winding the positive electrode sheet also has a lower water content accordingly, thereby improving the cycle performance of the secondary battery and extending the service life of the secondary battery.
[0058] In some embodiments, the compaction density of the positive electrode sheet is 2.35 to 2.6 g / cm 3 Therefore, when the compaction density of the positive electrode sheet is within the above range, the pores of the positive electrode sheet are moderate, which is conducive to the volatilization of water during the baking process.
[0059] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.
[0060] In one embodiment of the present application, a secondary battery is provided.
[0061] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0062] [Positive electrode]
[0063] The positive electrode sheet is the positive electrode sheet of the first aspect of the present application.
[0064] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0065] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0066] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0067] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0068] [Negative electrode]
[0069] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0070] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0071] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0072] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0073] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0074] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0075] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0076] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0077] [Electrolytes]
[0078] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0079] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0080] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0081] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0082] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0083] [Isolation film]
[0084] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0085] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0086] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0087] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0088] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0089] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 2 The secondary battery 5 is a square structure as an example.
[0090] In some embodiments, reference Figure 3 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0091] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0092] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0093] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0094] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0095] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0096] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0097] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0098] Figure 7 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0099] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0100] Example
[0101] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0102] Example 1
[0103] The positive electrode active material lithium iron phosphate, dehydrating agent A (sodium sulfate), conductive carbon, and PVDF were mixed in a mass ratio of 97.48:0.02:0.7:1.8 and added to N-methylpyrrolidone and stirred for 4 hours to obtain a positive electrode slurry. The obtained slurry was coated with a coating weight of CW = 0.35 g / 1540.25 mm 2 Coated on aluminum foil current collector, dried, cold pressed (density 2.5g / cm 3) to obtain the positive electrode sheet.
[0104] The drying temperature is 110°C, the drying time is 4 hours, the cold pressing speed is 5-50 m / min, the cold pressing pressure is 0.5-100 MPa, and the cold pressing gap is 50 μm-1 mm.
[0105] Example 2
[0106] Except that the mass ratio of the positive electrode active material lithium iron phosphate, dehydrating agent A (sodium sulfate), conductive carbon, and PVDF is changed to 97.41:0.09:0.7:1.8, the other conditions are the same as those in Example 1.
[0107] Example 3
[0108] Except that the mass ratio of the positive electrode active material lithium iron phosphate, dehydrating agent A (sodium sulfate), conductive carbon, and PVDF is changed to 97.2:0.3:0.7:1.8, the other conditions are the same as those in Example 1.
[0109] Example 4
[0110] Except that the mass ratio of the positive electrode active material lithium iron phosphate, dehydrating agent A (sodium sulfate), conductive carbon, and PVDF is changed to 96.5:1.0:0.7:1.8, the other conditions are the same as those in Example 1.
[0111] Example 5
[0112] Except that the mass ratio of the positive electrode active material lithium iron phosphate, dehydrating agent A (sodium sulfate), conductive carbon, and PVDF is changed to 95.5:2.0:0.7:1.8, the other conditions are the same as those in Example 1.
[0113] Example 6
[0114] The positive electrode active material lithium iron phosphate, dehydrating agent B (sodium dodecylbenzene sulfonate), conductive carbon, and PVDF were mixed in a mass ratio of 97.48:0.02:0.7:1.8 and added into N-methylpyrrolidone and stirred for 4 hours to obtain a positive electrode slurry. The obtained slurry was coated with a coating weight of CW = 0.35 g / 1540.25 mm 2 Coated on aluminum foil current collector, dried, cold pressed (density 2.5g / cm 3 ) to obtain the positive electrode sheet.
[0115] The drying temperature is 110°C, the drying time is 4 hours, the cold pressing speed is 5-50 m / min, the cold pressing pressure is 0.5-100 MPa, and the cold pressing gap is 50 μm-1 mm.
[0116] Example 7
[0117] Except that the mass ratio of the positive electrode active material lithium iron phosphate, dehydrating agent B (sodium dodecylbenzene sulfonate), conductive carbon, and PVDF is changed to 97.41:0.09:0.7:1.8, the other conditions are the same as those in Example 6.
[0118] Example 8
[0119] Except that the mass ratio of the positive electrode active material lithium iron phosphate, dehydrating agent B (sodium dodecylbenzene sulfonate), conductive carbon and PVDF is changed to 97.2:0.3:0.7:1.8, the other conditions are the same as those in Example 6.
[0120] Example 9
[0121] Except that the mass ratio of the positive electrode active material lithium iron phosphate, dehydrating agent B (sodium dodecylbenzene sulfonate), conductive carbon and PVDF is changed to 96.5:1.0:0.7:1.8, the other conditions are the same as those in Example 6.
[0122] Example 10
[0123] Except that the mass ratio of the positive electrode active material lithium iron phosphate, dehydrating agent B (sodium dodecylbenzene sulfonate), conductive carbon and PVDF is changed to 95.5:2.0:0.7:1.8, the other conditions are the same as those in Example 6.
[0124] Embodiment 11
[0125] The positive electrode active material lithium iron phosphate, dehydrating agent C (potassium perfluorooctane sulfonate), conductive carbon, and PVDF were mixed in a mass ratio of 97.48:0.02:0.7:1.8 and added to N-methylpyrrolidone and stirred for 4 hours to obtain a positive electrode slurry. The obtained slurry was coated with a coating weight of CW = 0.35 g / 1540.25 mm 2 Coated on aluminum foil current collector, dried, cold pressed (density 2.5g / cm 3 ) to obtain the positive electrode sheet.
[0126] The drying temperature is 110°C, the drying time is 4 hours, the cold pressing speed is 5-50 m / min, the cold pressing pressure is 0.5-100 MPa, and the cold pressing gap is 50 μm-1 mm.
[0127] Example 12
[0128] Except that the mass ratio of the positive electrode active material lithium iron phosphate, desiccant C (potassium perfluorooctane sulfonate), conductive carbon, and PVDF is changed to 97.41:0.09:0.7:1.8, the other conditions are the same as those in Example 11.
[0129] Embodiment 13
[0130] Except that the mass ratio of the positive electrode active material lithium iron phosphate, desiccant C (potassium perfluorooctane sulfonate), conductive carbon, and PVDF is changed to 97.2:0.3:0.7:1.8, the other conditions are the same as those in Example 11.
[0131] Embodiment 14
[0132] Except that the mass ratio of the positive electrode active material lithium iron phosphate, desiccant C (potassium perfluorooctane sulfonate), conductive carbon, and PVDF is changed to 96.5:1.0:0.7:1.8, the other conditions are the same as those in Example 11.
[0133] Embodiment 15
[0134] Except that the mass ratio of the positive electrode active material lithium iron phosphate, desiccant C (potassium perfluorooctane sulfonate), conductive carbon, and PVDF is changed to 95.5:2.0:0.7:1.8, the other conditions are the same as those in Example 11.
[0135] Example 16
[0136] The positive electrode active material lithium iron phosphate, dehydrating agent D (octylphenol polyoxyethylene ether), conductive carbon, and PVDF were mixed in a mass ratio of 97.48:0.02:0.7:1.8 and added into N-methylpyrrolidone and stirred for 4 hours to obtain a positive electrode slurry. The obtained slurry was coated with a coating weight of CW = 0.35 g / 1540.25 mm 2 Coated on aluminum foil current collector, dried, cold pressed (density 2.5g / cm 3 ) to obtain the positive electrode sheet.
[0137] The drying temperature is 110°C, the drying time is 4 hours, the cold pressing speed is 5-50 m / min, the cold pressing pressure is 0.5-100 MPa, and the cold pressing gap is 50 μm-1 mm.
[0138] Embodiment 17
[0139] Except that the mass ratio of the positive electrode active material lithium iron phosphate, desiccant D (octylphenol polyoxyethylene ether), conductive carbon, and PVDF is changed to 97.41:0.09:0.7:1.8, the other conditions are the same as those in Example 16.
[0140] Embodiment 18
[0141] Except that the mass ratio of the positive electrode active material lithium iron phosphate, desiccant D (octylphenol polyoxyethylene ether), conductive carbon, and PVDF is changed to 97.2:0.3:0.7:1.8, the other conditions are the same as those in Example 16.
[0142] Embodiment 19
[0143] Except that the mass ratio of the positive electrode active material lithium iron phosphate, desiccant D (octylphenol polyoxyethylene ether), conductive carbon, and PVDF is changed to 96.5:1.0:0.7:1.8, the other conditions are the same as those in Example 16.
[0144] Embodiment 20
[0145] Except that the mass ratio of the positive electrode active material lithium iron phosphate, desiccant D (octylphenol polyoxyethylene ether), conductive carbon, and PVDF is changed to 95.5:2.0:0.7:1.8, the other conditions are the same as those in Example 16.
[0146] Embodiment 21
[0147] The positive electrode active material lithium iron phosphate, dehydrating agent A+B, conductive carbon, and PVDF were mixed in a mass ratio of 97.2:0.3:0.7:1.8 and added to N-methylpyrrolidone and stirred for 4 hours to obtain a positive electrode slurry. The obtained slurry was coated with a coating weight of CW=0.35g / 1540.25mm 2 Coated on aluminum foil current collector, dried, cold pressed (density 2.5g / cm 3 ), and then the positive electrode sheet is obtained. The weight proportion of the dehydrating agent A is 0.05-0.15%, and the weight proportion of the dehydrating agent B is 0.15-0.25%.
[0148] The drying temperature is 110°C, the drying time is 4 hours, the cold pressing speed is 5-50 m / min, the cold pressing pressure is 0.5-100 MPa, and the cold pressing gap is 50 μm-1 mm.
[0149] Embodiment 22
[0150] Except for selecting dewatering agents A+C, wherein the weight proportion of dewatering agent A is 0.05-0.15% and the weight proportion of dewatering agent C is 0.15-0.25%, other conditions are the same as those in Example 21.
[0151] Embodiment 23
[0152] Except for selecting dehydrating agents A+D, wherein the weight proportion of dehydrating agent A is 0.05-0.15% and the weight proportion of dehydrating agent D is 0.15-0.25%, other conditions are the same as those in Example 21.
[0153] Embodiment 24
[0154] The positive electrode active material lithium iron phosphate, dehydrating agent B+C, conductive carbon, and PVDF were mixed in a mass ratio of 97.2:0.3:0.7:1.8 and added to N-methylpyrrolidone and stirred for 4 hours to obtain a positive electrode slurry. The obtained slurry was coated with a coating weight of CW=0.35g / 1540.25mm 2Coated on aluminum foil current collector, dried, cold pressed (density 2.5g / cm 3 ), and then the positive electrode sheet is obtained. The weight proportion of the dehydrating agent B is 0.05-0.15%, and the weight proportion of the dehydrating agent C is 0.15-0.25%.
[0155] The drying temperature is 110°C, the drying time is 4 hours, the cold pressing speed is 5-50 m / min, the cold pressing pressure is 0.5-100 MPa, and the cold pressing gap is 50 μm-1 mm.
[0156] Embodiment 25
[0157] Except for selecting dehydrating agent B+D, wherein the weight proportion of dehydrating agent B is 0.05-0.15% and the weight proportion of dehydrating agent D is 0.15-0.25%, other conditions are the same as those in Example 24.
[0158] Embodiment 26
[0159] The positive electrode active material lithium iron phosphate, dehydrating agent C+D, conductive carbon, and PVDF were mixed in a mass ratio of 97.2:0.3:0.7:1.8 and added to N-methylpyrrolidone and stirred for 4 hours to obtain a positive electrode slurry. The obtained slurry was coated with a coating weight of CW=0.35g / 1540.25mm 2 Coated on aluminum foil current collector, dried, cold pressed (density 2.5g / cm 3 ), and then the positive electrode sheet is obtained. The weight proportion of the dehydrating agent C is 0.05-0.15%, and the weight proportion of the dehydrating agent D is 0.15-0.25%.
[0160] The drying temperature is 110°C, the drying time is 4 hours, the cold pressing speed is 5-50 m / min, the cold pressing pressure is 0.5-100 MPa, and the cold pressing gap is 50 μm-1 mm.
[0161] Embodiment 27
[0162] The positive electrode active material lithium iron phosphate, dehydrating agent B+C+D, conductive carbon, and PVDF were mixed in a mass ratio of 97.2:0.3:0.7:1.8 and added to N-methylpyrrolidone and stirred for 4 hours to obtain a positive electrode slurry. The obtained slurry was coated with a coating weight of CW=0.35g / 1540.25mm 2 Coated on aluminum foil current collector, dried, cold pressed (density 2.5g / cm 3 ), and then the positive electrode sheet is obtained. The weight proportion of the dehydrating agent B is 0.01-0.1%, the weight proportion of the dehydrating agent C is 0.05-0.15%, and the weight proportion of the dehydrating agent D is 0.15-0.20%.
[0163] The drying temperature is 110°C, the drying time is 4 hours, the cold pressing speed is 5-50 m / min, the cold pressing pressure is 0.5-100 MPa, and the cold pressing gap is 50 μm-1 mm.
[0164] Embodiment 28
[0165] The positive electrode active material lithium iron phosphate, dehydrating agent A+B+C+D, conductive carbon and PVDF were mixed in a mass ratio of 97.2:0.3:0.7:1.8 and added into N-methylpyrrolidone and stirred for 4 hours to obtain a positive electrode slurry. The obtained slurry was coated with a coating weight of CW=0.35g / 1540.25mm 2 Coated on aluminum foil current collector, dried, cold pressed (density 2.5g / cm 3 ), and then the positive electrode sheet is obtained. Among them, the weight proportion of dehydrating agent A is 0.01-0.1%, the weight proportion of dehydrating agent B is 0.01-0.1%, the weight proportion of dehydrating agent C is 0.05-0.15%, and the weight proportion of dehydrating agent D is 0.15-0.20%.
[0166] The drying temperature is 110°C, the drying time is 4 hours, the cold pressing speed is 5-50 m / min, the cold pressing pressure is 0.5-100 MPa, and the cold pressing gap is 50 μm-1 mm.
[0167] Comparative Example 1
[0168] The positive electrode active material lithium iron phosphate, conductive carbon, and PVDF were mixed in a mass ratio of 97.5:0.7:1.8 and added to N-methylpyrrolidone and stirred for 4 hours to obtain a positive electrode slurry. The obtained slurry was coated with a coating weight of CW = 0.35 g / 1540.25 mm 2 Coated on aluminum foil current collector, dried, cold pressed (density 2.5g / cm 3 ) to obtain the positive electrode sheet.
[0169] The drying temperature is 110°C, the drying time is 6 hours, the cold pressing speed is 5-50 m / min, the cold pressing pressure is 0.5-100 MPa, and the cold pressing gap is 50 μm-1 mm.
[0170] Comparative Example 2
[0171] The positive electrode active material lithium iron phosphate, dehydrating agent A (sodium sulfate), conductive carbon, and PVDF were mixed in a mass ratio of 92.5:5.0:0.7:1.8 and added to N-methylpyrrolidone and stirred for 4 hours to obtain a positive electrode slurry. The obtained slurry was coated with a coating weight of CW = 0.35 g / 1540.25 mm 2 Coated on aluminum foil current collector, dried, cold pressed (density 2.5g / cm 3 ) to obtain the positive electrode sheet.
[0172] The drying temperature is 110°C, the drying time is 4 hours, the cold pressing speed is 5-50 m / min, the cold pressing pressure is 0.5-100 MPa, and the cold pressing gap is 50 μm-1 mm.
[0173] Comparative Example 3
[0174] Except that the dehydrating agent was replaced with dehydrating agent B (sodium dodecylbenzene sulfonate), the other conditions were the same as those of Comparative Example 2.
[0175] Comparative Example 4
[0176] Except that the dehydrating agent was replaced with dehydrating agent C (potassium perfluorooctane sulfonate), the other conditions were the same as those of Comparative Example 2.
[0177] Comparative Example 5
[0178] Except that the dehydrating agent was replaced with dehydrating agent D (octylphenol polyoxyethylene ether), the other conditions were the same as those of Comparative Example 2.
[0179] Comparative Example 6
[0180] The positive electrode active material lithium iron phosphate, dehydrating agent A+B+C+D, conductive carbon, and PVDF were mixed in a mass ratio of 92.5:5.0:0.7:1.8 and added into N-methylpyrrolidone and stirred for 4 hours to obtain a positive electrode slurry. The obtained slurry was coated with a coating weight of CW=0.35g / 1540.25mm 2 Coated on aluminum foil current collector, dried, cold pressed (density 2.5g / cm 3 ) to obtain the positive electrode sheet.
[0181] The drying temperature is 110°C, the drying time is 4 hours, the cold pressing speed is 5-50 m / min, the cold pressing pressure is 0.5-100 MPa, and the cold pressing gap is 50 μm-1 mm.
[0182] The relevant parameters of the positive electrode materials of the above-mentioned Examples 1 to 28 and Comparative Examples 1 to 6 are shown in the following Table 1.
[0183] Table 1: Parameter results of Examples 1 to 28 and Comparative Examples 1 to 6
[0184] Dewatering agent type Dehydration agent content Comparative Example 1 / 0.00% Comparative Example 2 A 5.00% Comparative Example 3 B 5.00% Comparative Example 4 C 5.00% Comparative Example 5 D 5.00% Comparative Example 6 A+B+C+D 5.00% Example 1 A 0.02% Example 2 A 0.09% Example 3 A 0.30% Example 4 A 1.00% Example 5 A 2.00% Example 6 B 0.02% Example 7 B 0.09% Example 8 B 0.30% Example 9 B 1.00% Example 10 B 2.00% Embodiment 11 C 0.02% Example 12 C 0.09% Example 13 C 0.30% Embodiment 14 C 1.00% Embodiment 15 C 2.00% Example 16 D 0.02% Embodiment 17 D 0.09% Embodiment 18 D 0.30% Embodiment 19 D 1.00% Embodiment 20 D 2.00% Embodiment 21 A+B 0.30% Embodiment 22 A+C 0.30% Embodiment 23 A+D 0.30% Embodiment 24 B+C 0.30% Embodiment 25 B+D 0.30% Embodiment 26 C+D 0.30% Embodiment 27 B+C+D 0.30% Embodiment 28 A+B+C+D 0.30%
[0185] In addition, the positive electrode active materials obtained in the above Examples 1 to 28 and Comparative Examples 1 to 6 were respectively prepared into button cells and secondary batteries as shown below, and performance tests were performed. The test results are shown in Table 2 below.
[0186] (1) Preparation of button cells
[0187] The positive electrode sheets in the above-mentioned embodiments and comparative examples are used, the lithium sheet is used as the negative electrode, the electrolyte is 1 mol / LLiPF6 / (ethylene carbonate (EC) + diethyl carbonate (DEC) + dimethyl carbonate (DMC)) (volume ratio 1:1:1), and button batteries are assembled in a button box.
[0188] (2) Initial gram capacity test of button cell
[0189] Each button cell prepared as above was charged to 4.0 V at 0.05 C at 2.0-4.0 V, then charged at a constant voltage at 4.0 V to a current ≤ 0.05 mA, allowed to stand for 5 minutes, and then discharged to 2.0 V at 0.05 C. The discharge capacity at this time is the initial discharge capacity, recorded as D0. The tested discharge capacity value (i.e., the initial discharge capacity D0) was divided by the mass of the positive electrode active material in the button cell, which is the initial gram capacity of the button cell of the positive electrode sheet.
[0190] (3) Preparation of secondary batteries
[0191] The positive electrode plate is selected from the positive electrode plates in the above-mentioned embodiments and comparative examples.
[0192] Artificial graphite as a negative electrode active material, acetylene black as a conductive agent, styrene butadiene rubber (SBR) as a binder, and carbon methyl cellulose sodium (CMC) as a thickener are fully stirred and mixed in a deionized water solvent system in a weight ratio of 90:5:2:2:1, and then coated on a copper foil, dried, and cold pressed to obtain a negative electrode sheet.
[0193] A porous polymer film made of polyethylene (PE) is used as the isolation membrane.
[0194] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrodes to play a role of isolation, and then wound to obtain a bare cell. The bare cell is placed in an outer package and vacuum-baked at a negative pressure of 100 kPa. After the baking is completed, the electrolyte is injected and packaged to obtain a secondary battery.
[0195] (4) The first coulombic efficiency test of secondary batteries
[0196] After formation, each secondary battery prepared as above was placed at a constant temperature of 25°C for 5 minutes, discharged to 2.0V at 1C, placed for 10 minutes, charged to 3.8V at 1C, then charged at a constant voltage at 3.8V to a current ≤0.05mA, placed for 30 minutes, and the charging capacity at this time was recorded as C1, and then discharged to 2.0V at 1C, and the discharge capacity at this time was the initial discharge capacity, recorded as D1.
[0197] First coulomb efficiency = initial discharge capacity D1 / (first charge capacity C1+chemical film formation consumption C0-D0)
[0198] First efficiency difference = first coulombic efficiency of example n - first coulombic efficiency of comparative example 1 (n = 1, 2, 3...)
[0199] Among them, C0 is the charge capacity during formation, D0 is the discharge capacity after formation, D1 is the first discharge capacity, and C1 is the first charge capacity.
[0200] (5) Secondary battery cycle performance test at 25°C
[0201] Each secondary battery prepared above was charged to 3.8V at 1C at 2.0-3.8V under a constant temperature environment of 25°C, then charged at a constant voltage at 3.8V to a current of ≤0.05mA, left to stand for 10 minutes, and then discharged to 2.0V at 1C. The capacity was recorded as D n (n=0, 1, 2...), repeat the above operation for 600 cycles, and measure the capacity fading value.
[0202] Capacity retention rate = (D 600 / Battery nominal capacity (161Ah) * 100%
[0203] Cycle attenuation difference = capacity retention rate of Example n - capacity retention rate of Comparative Example 1 (n = 1, 2, 3...)
[0204] Table 2: Performance test results of Examples 1 to 28 and Comparative Examples 1 to 6
[0205]
[0206]
[0207] According to the above results, Examples 1 to 28 increase the saturated vapor pressure of water stored in the capillary structure between particles by adding nonionic surfactants and ionic surfactants to the positive electrode sheets, thereby achieving good results in removing water from the positive electrode sheets. In addition, the water removal rate of the positive electrode sheets and the cycle performance and first coulomb efficiency of the secondary battery using the positive electrode sheets are also improved.
[0208] In contrast, the positive electrode sheet in Comparative Example 1 does not contain any dehydrating agent, so no significant effect is achieved in the dehydration rate of the positive electrode sheet, and the cycle performance and the first coulomb efficiency of the secondary battery are also inferior to those of Examples 1 to 28. In addition, dehydrating agent A (sodium sulfate) is used in Comparative Example 2, and its weight ratio is 5.0%; dehydrating agent B (sodium dodecylbenzene sulfonate) is used in Comparative Example 3, and its weight ratio is 5.0%; dehydrating agent C (potassium perfluorooctane sulfonate) is used in Comparative Example 4, and its weight ratio is 5.0%; dehydrating agent D (octylphenol polyoxyethylene ether) is used in Comparative Example 5, and its weight ratio is 5.0%; dehydrating agent A+B+C+D is used in Comparative Example 6, and its total mass ratio is as high as 5.0%; the use of dehydrating agent improves the dehydration performance of the positive electrode sheet, but affects the initial discharge gram capacity of the secondary battery, which is not conducive to the energy density of the secondary battery.
[0209] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode sheet comprises: a current collector and a coating applied to at least one surface of the current collector. The coating comprises a positive electrode active material and a water removing agent, The positive electrode active material is lithium iron phosphate, Relative to the total solid content of the coating, the weight proportion of the dehydrating agent is 0.02% to 2.0%.
2. The positive electrode sheet according to claim 1, characterized in that: The weight proportion of the dehydrating agent is 0.09% to 0.3%.
3. The positive electrode sheet according to claim 1, characterized in that: The dewatering agent is at least one of a nonionic surfactant and an ionic surfactant.
4. The positive electrode sheet according to claim 3, characterized in that: The ionic surfactant is at least one of sulfate and alkylphenyl sulfonate. And / or, the nonionic surfactant is at least one of octylphenol polyoxyethylene ether and polyvinyl pyrrolidone.
5. The positive electrode sheet according to claim 4, characterized in that: The sulfate is at least one of sodium sulfate and potassium sulfate, and the alkylphenyl sulfonate is at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and potassium perfluorooctane sulfonate.
6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: Relative to the total weight of the coating, the total weight ratio of the lithium iron phosphate and the dehydrating agent is 95-98%.
7. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The compaction density of the positive electrode sheet is 2.35 g / cm 3 ~2.6g / cm 3 .
8. A secondary battery, characterized in that: A positive electrode sheet comprising the positive electrode sheet according to any one of claims 1 to 7.
9. A battery module, characterized in that: A secondary battery comprising the secondary battery as claimed in claim 8.
10. A battery pack, characterized in that: A battery module comprising the battery module described in claim 9.
11. An electrical device, characterized in that: The battery comprises at least one selected from the secondary battery of claim 8, the battery module of claim 9, or the battery pack of claim 10.
Citation Information
Patent Citations
Graphite alkene iron lithium phosphate positive active material, preparing method thereof, and lithium ion twice battery based on the graphite alkene modified iron lithium phosphate positive active material
CN101752561A
High-power lithium ion battery for automobile start-stop power supply
CN112582667A